Improving the Monetary Policy Frameworks in Central America - Medina Cas, Stephanie (IMF Working Papers; Working Paper, 2011)
Several Central American (CADR) countries with independent monetary policies are strengthening their monetary frameworks and some have implemented or are moving towards inflation targeting (IT) regimes. Strengthening the monetary policy frameworks of CADR is key to improving the effectiveness of monetary policy. The paper reviews the literature on the reforms needed for strengthening the monetary policy frameworks, and examines the experiences of IT countries, Chile, Peru, and Uruguay to help distill lessons for CADR. It also constructs an index to measure the relative strength of the monetary policy framework of CADR countries.